A Trial of Calcium and Vitamin D for the Prevention of Colorectal Adenomas - Baron, John A. (N Engl J Med, 2015)
BACKGROUND: Epidemiologic and preclinical data suggest that higher intake and serum levels of vitamin D and higher intake of calcium reduce the risk of colorectal neoplasia. To further study the chemopreventive potential of these nutrients, we conducted a randomized, double-blind, placebo-controlled trial of supplementation with vitamin D, calcium, or both for the prevention of colorectal adenomas. METHODS: We recruited patients with recently diagnosed adenomas and no known colorectal polyps remaining after complete colonoscopy. We randomly assigned 2259 participants to receive daily vitamin D(3) (1000 IU), calcium as carbonate (1200 mg), both, or neither in a partial 2×2 factorial design. Women could elect to receive calcium plus random assignment to vitamin D or placebo. Follow-up colonoscopy was anticipated to be performed 3 or 5 years after the baseline examinations, according to the endoscopist’s recommendation. The primary end point was adenomas diagnosed in the interval from randomization through the anticipated surveillance colonoscopy. RESULTS: Participants who were randomly assigned to receive vitamin D had a mean net increase in serum 25-hydroxyvitamin D levels of 7.83 ng per milliliter, relative to participants given placebo. Overall, 43% of participants had one or more adenomas diagnosed during follow-up. The adjusted risk ratios for recurrent adenomas were 0.99 (95% confidence interval [CI], 0.89 to 1.09) with vitamin D versus no vitamin D, 0.95 (95% CI, 0.85 to 1.06) with calcium versus no calcium, and 0.93 (95% CI, 0.80 to 1.08) with both agents versus neither agent. The findings for advanced adenomas were similar. There were few serious adverse events. CONCLUSIONS: Daily supplementation with vitamin D(3) (1000 IU), calcium (1200 mg), or both after removal of colorectal adenomas did not significantly reduce the risk of recurrent colorectal adenomas over a period of 3 to 5 years. (Funded by the National Cancer Institute; ClinicalTrials.gov number, NCT00153816.)